(untitled) (Damascus University Journal of agriculture sciences, 2021)
In this study,spectral signature during wavelength range (350-2500nm) of soils in Yahmor and Miaar plane/Tartous were determined. Organic matter in that area were estimated depending on the best spectral model during each category by: 1” reflectance value at wavelength (λ568nm) using exponential equation[OM= 141.62e-31.23λ568]. 2” band (B3) using exponential equation [OM= 130.62e-30.61B3]. 3” ratio bands (B8/B6) using logarithmic equation [OM= 0.0332*Log(B8/B6) +0.02629]. 4” normalized bands (B8-B6)/( B8+B6) using logarithmic equation [OM= 0.0301*Log( ) -0.79915]. Determination coefficient for models of: wavelength, bands, ratio bands and normalized bands were 0.693, 0.771, 0.487 and 0.53, respectively. Accuracy estimation of OM by image opposite actual reach 82% at field level. OM distribution map using Sentinel-2 image depending on the best field spectral model were mapping for Yahmor and Miaar plane/Tartous.